Critical information infrastructures security : 8th international workshop, CRITIS 2013, Amsterdam, The Netherlands, September 16-18, 2013, Revised Selected Papers - Hartel, Pieter (Lecture Notes in Computer Science,, 2013)
This book constitutes the thoroughly refereed post-proceedings of the 8th International Workshop on Critical Information Infrastructures Security, CRITIS 2013, held in Amsterdam, The Netherlands, in September 2013. The 16 revised full papers and 4 short papers were thoroughly reviewed and selected from 57 submissions. The papers are structured in the following topical sections: new challenges, natural disasters, smart grids, threats and risk, and SCADA/ICS and sensors.